2014
DOI: 10.1186/1471-2318-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Is the Timed Up and Go test a useful predictor of risk of falls in community dwelling older adults: a systematic review and meta- analysis

Abstract: BackgroundThe Timed Up and Go test (TUG) is a commonly used screening tool to assist clinicians to identify patients at risk of falling. The purpose of this systematic review and meta-analysis is to determine the overall predictive value of the TUG in community-dwelling older adults.MethodsA literature search was performed to identify all studies that validated the TUG test. The methodological quality of the selected studies was assessed using the QUADAS-2 tool, a validated tool for the quality assessment of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
567
5
41

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(637 citation statements)
references
References 53 publications
24
567
5
41
Order By: Relevance
“…The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four. Then came China (26,50,73) , France (45,49,74) and Sweden (37)(38)41) , with two, Ireland (75)(76) with one, and Germany (21) , Brazil (16) , Korea (26) , Spain (77) , Japan (22) , and Thailand (43) . Six of the selected studies are secondary (systematic literature reviews) and the remaining 56 are primary studies based on quantitative methodology, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four. Then came China (26,50,73) , France (45,49,74) and Sweden (37)(38)41) , with two, Ireland (75)(76) with one, and Germany (21) , Brazil (16) , Korea (26) , Spain (77) , Japan (22) , and Thailand (43) . Six of the selected studies are secondary (systematic literature reviews) and the remaining 56 are primary studies based on quantitative methodology, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The regression model constructed in this way explained 43% of variance in the TUG test results. Taking into account that the TUG test outcome reflects muscle strength, balance, and mobility [30], the adjusted R 2 coefficient for the model seems to be satisfactory. However, when searching the available literature, the authors found some contradictory data on the TUG test usefulness and reliability.…”
Section: Discussionmentioning
confidence: 91%
“…However, when searching the available literature, the authors found some contradictory data on the TUG test usefulness and reliability. A systematic review and metaanalysis conducted by barry et al [30] imply that the predictive value of this test is relatively limited. According to these authors, balance, leg muscle strength, and mobility, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Sua praticidade, rapidez e baixo custo, tornam o TUGT um teste largamente utilizado em pesquisas e no âmbito clínico. 14,15,16 O objetivo deste estudo foi investigar a mobilidade funcional de idosos frágeis institucionalizados e a sua relação com as características clínicas mais importantes, ou seja, a sarcopenia e a dinapenia, ambas passíveis de intervenções preventivas e terapêuticas. …”
Section: Introductionunclassified